2016
DOI: 10.1111/jfq.12238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cocoa Hybrids on Volatile Compounds of Fermented Beans, Microbial Diversity during Fermentation and Sensory Characteristics and Acceptance of Chocolates

Abstract: Microbial diversity, final concentration of volatiles compounds during fermentation and the characterization and acceptability of chocolates of three cocoa hybrids (PH 9, PH 15 and PH 16) were evaluated. Hanseniaspora uvarum, Pichia kluyveri, Pichia caribbica and Saccharomyces cerevisiae were the predominant yeasts in the three fermentations. Lactobacillus plantarum, Acetobacter pasteurianus, Bacillus cereus and Lysinibacillus fusiformis were the common bacterial species isolated from the fermentations. The PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In Figure 5, presumptive B. cereus was able to grow up reaching to 8.0 log 10 CFU/mL at 35°C for 6 hours which is not safe for human consumption. Magalhães da Veiga Moreira et al, (2016) reported that yeast, B. cereus, and Bacillus spp. are commonly isolated from fermentation of cocoa.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 5, presumptive B. cereus was able to grow up reaching to 8.0 log 10 CFU/mL at 35°C for 6 hours which is not safe for human consumption. Magalhães da Veiga Moreira et al, (2016) reported that yeast, B. cereus, and Bacillus spp. are commonly isolated from fermentation of cocoa.…”
Section: Resultsmentioning
confidence: 99%
“…Yeasts produced ethanol from sugars, and LAB produced lactic acid, acetic acid, ethanol, and mannitol from sugars and/or citrate (Camu et al., 2007; Papalexandratou et al., 2013). The experiment conducted by (Magalhães da Veiga Moreira et al., 2016) in Porto Híbrido 9, Porto Híbrido 15 and Porto Híbrido 16 cocoa beans at the Vale do Juliana farm in Igrapiúna, Bahia, Brazil, Hanseniaspora uvarum , P. kluyveri , P. caribbica and S. cerevisiae were the predominant yeasts in the three fermentations. L. plantarum , A. pasteurianus , Bacillus cereus and Lysinibacillus fusiformis were the common bacterial species isolated from the fermentations.…”
Section: Main Textmentioning
confidence: 99%
“…LAB can also metabolize sugars and organic acids to produce various aldehydes, ketones and other volatile components that can impact the sensory quality of the bean (Ardhana, 2003). It is known that some compounds come from the metabolism of yeasts, such as phenylethylacetate (fruit, sweet, honey (Magalhães da Veiga Moreira et al., 2016)), 2-phenylethanol (honey, floral (Magalhães da Veiga Moreira et al., 2016)), 2-phenylacetic acid and acetoin (butter, cream (Batista et al., 2016; Visintin et al., 2017)). Table 4 shows that in the fermentation of cocoa hybrids controlled by a starter culture, it is possible to obtain aromatic compounds identified in Criollo cocoa (Crafack et al., 2014; Batista et al., 2016; Visintin et al., 2017; Magalhães da Veiga Moreira et al., 2017).…”
Section: Main Textmentioning
confidence: 99%
“…Undesirable and pungent features are associated with the presence of hexanoic acid, believed to be a compound that imparts unpleasant taste and aroma to chocolate products (da Veiga Moreira et al 2016). These authors showed a correlation between astringency, bitterness, acrid flavour, and content of propanoic acid.…”
Section: Resultsmentioning
confidence: 95%